2002
DOI: 10.1007/s00330-002-1657-y
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of lymphomatoid granulomatosis: punctate and linear enhancement preceding hemorrhage

Abstract: Lymphomatoid granulomatosis (LG) is an angiocentric and angiodestructive lymphoproliferative disease that mainly involves the lung. Thirty percent of patients with LG have neurological symptoms. We report serial changes in MRI of a patient with LG of the brain. Postcontrast MRI demonstrated multiple punctate and linear areas that preceded hemorrhage, as indicated by hypointensity with surrounding hyperintensity on subsequent T2-weighted images. The diagnostic value of these lesions observed with contrast MR im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
4
1
Order By: Relevance
“…These results suggest that spinal LYG is rarer than brain LYG. Spinal LYG was found to be more prevalent in men than in women in this study (6.5:1.0) than in previous reports (systemic LYG; 2:1 13 and isolated CNS LYG; 2.3:1.0 2 ). Moreover, the lung lesion is the most common LYG lesion, although only 42.9% had lung lesions and 6 cases were isolated CNS LYG cases in our series.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…These results suggest that spinal LYG is rarer than brain LYG. Spinal LYG was found to be more prevalent in men than in women in this study (6.5:1.0) than in previous reports (systemic LYG; 2:1 13 and isolated CNS LYG; 2.3:1.0 2 ). Moreover, the lung lesion is the most common LYG lesion, although only 42.9% had lung lesions and 6 cases were isolated CNS LYG cases in our series.…”
Section: Discussioncontrasting
confidence: 76%
“…By further application of strict inclusion and exclusion criteria, 14 articles were included in our final analysis ( Figure 3 ). 1 , 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 In this study, 15 cases, including our 1 case, were investigated ( Table 1 ).
Figure 3 Systematic literature search for spinal lymphomatoid granulomatosis according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines.
…”
Section: Systematic Review Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Neurological symptoms occur in 30% of the cases 3 and sometimes represent the only manifestation of the disease. 4 Several studies [5][6][7][8] reported progressive lesion volume on MRI in LG but only a few reports 9,10 described brain atrophy. There are no reported cases of NP test performance in patients with LG, save one report of borderline IQ.…”
mentioning
confidence: 99%
“…70 Multifocal involvement on brain MR imaging is commonplace, with punctate or linear T2 hyperintensities within perivascular spaces with corresponding enhancement on T1 postcontrast images, particularly within frontal and parietal regions-a finding not exclusive to LG and seen in angiitis and neurosarcoidosis but distinguishable from CNS lymphoma, which most often presents as a solitary lesion. [70][71][72][73] …”
mentioning
confidence: 99%